Awareness, Attitude and Probable Area of Difficulties towards the Proposed Goods and Services Tax in Malaysia - Marimuthu, Munusamy; Bidin, Zainol (International Review of Management and Marketing, 2016)
Malaysian Government wanted to implement Goods and Services Tax (GST) once everyone familiar with the tax. This study is aimed to explore the level of awareness, attitude, and identifying probable area of difficulties among managers of manufacturing companies in Malaysia towards the proposed GST. A survey was carried out to acquire the data from 1,500 managers of manufacturing companies throughout Malaysia using questionnaire with a response rate of 13.4% (201) response rate. Result of reliability and validity shows the cronbach alpha value and KMO value have more than 0.70 for all the three (3) constructs and all the items in these constructs have mean score of above 3.00. The result indicated that managers of manufacturing companies in Malaysia have high level of awareness, positive attitude and agreed to the potential area of difficulties towards the Government intention to introduce GST. Keywords: Awareness, Attitude, Probable Area of Difficulties. JEL Classification: H25